Washable flame-retardant cotton fabric and preparation method thereof

By sorting homemade N-P-Si flame retardant on cotton textiles, the problem of existing flame retardant cotton fabrics producing toxic substances and insufficient washing resistance during combustion is solved, and efficient flame retardant effect and thermal stability are achieved Improved, suitable for the safety needs of home bedding.

CN119265945AActive Publication Date: 2025-01-07HUIZHOU SIHAI JIANCHENG IND CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411583846.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-07
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing flame-retardant cotton fabrics produce toxic and harmful substances during combustion, which have poor thermal stability and insufficient water-resistant resistance, making it difficult to meet the safety needs of bedding in homes and daily life.

Method used

The homemade N-P-Si type flame retardant is used to form multi-group flame retardant molecules through chemical bonding, which is organized on cotton textiles to improve their thermal stability and flame retardant efficiency, and enhance their water-washing resistance through hydrogen bonding.

Benefits of technology

It achieves efficient flame retardant effect and thermal stability improvement. The cotton fabric still maintains good flame retardant performance after 50 washes without affecting the whiteness and mechanical properties of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265945A_ABST
    Figure CN119265945A_ABST
Patent Text Reader

Abstract

The invention provides a washable flame-retardant cotton fabric and a preparation method thereof, and the washable flame-retardant cotton fabric is characterized in that the washable flame-retardant cotton fabric is obtained by treating a cotton fabric with a flame-retardant finishing liquid containing an N-P-Si flame retardant; the N-P-Si type flame retardant contains N-based, P-based and Si-based multiple flame-retardant groups, has excellent thermal stability, self-charring capability and flame-retardant efficiency, and endows cotton fabrics with high limit oxygen index and flame-retardant effect when being used for finishing the cotton fabrics; the flame retardant can be bonded with cotton fabric fiber molecules through a strong hydrogen bond, so that the flame-retardant cotton fabric of which the surface is loaded with the N-P-Si type flame retardant has excellent washing resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of functional textiles, and specifically relates to a washable flame-retardant cotton fabric and a preparation method thereof. Background Art

[0002] Flame-retardant fiber, also known as flame-retardant fiber, refers to a fiber that only smolders in a flame, does not produce flames itself, and extinguishes itself when it leaves the flame. It is widely used in clothing, home furnishings, decoration, non-woven fabrics and fillings. Compared with ordinary fibers, flame-retardant fibers have significantly lower flammability, significantly slow down the burning rate during the combustion process, can quickly extinguish itself after leaving the fire source, and release less toxic smoke. Generally speaking, flame-retardant fibers are mainly concentrated in the field of synthetic fibers. For example, inorganic polymer flame retardants exist in the nano state or in the state of interpenetrating networks in the organic macromolecules of viscose fibers to produce fiber fabrics with flame retardant effects, which are suitable for use in fire suits, work clothes and other fields. However, mattresses, sheets, quilt covers and other bedding in home life are mainly made of cotton fabrics, and these places are also at high risk of fires caused by cigarette butts, electrical failures, etc., so the development and application of flame-retardant cotton fabrics are of great significance.

[0003] In the prior art, flame retardant cotton fabrics are usually introduced or fixed on the surface of cotton fabrics by physical adsorption or forming covalent bonds. Among the commonly used flame retardants, halogen flame retardants have been banned in some countries and regions because they produce toxic and harmful substances such as dioxins and hydrogen halide gases during combustion, which endanger human life, health and the environment; the chemical bonds formed by organophosphorus flame retardants on the surface of cotton fabrics are unstable, have poor thermal stability and are easy to volatilize; intumescent flame retardants are highly efficient and contain more water-soluble groups, and have poor water washability; silicon flame retardants have poor flame retardant effects and will affect the comfort and strength of cotton fabrics.

[0004] Therefore, there is an urgent need to develop new flame-retardant cotton fabrics and flame retardants to solve the problems of low flame retardant efficiency and poor water washability of cotton fabrics. Summary of the invention

[0005] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a washable flame-retardant cotton fabric and a preparation method thereof, and a cotton fabric with washable flame-retardant effect can be obtained by finishing the cotton textile with a homemade NP-Si type flame retardant.

[0006] As one aspect of the present invention, the present invention provides a washable flame-retardant cotton fabric, wherein the washable flame-retardant cotton fabric is prepared by treating the cotton fabric with a flame-retardant finishing liquid containing an NP-Si type flame retardant; the NP-Si type flame retardant has a molecular structure as shown in Formula I:

[0007]

[0008] Furthermore, the NP-Si type flame retardant is synthesized by the following steps:

[0009] S1. Under nitrogen protection, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) was dissolved in tetrahydrofuran, 4-bromocinnamic acid was added to the reaction system within 0.5 h at 80-90 °C, and then the temperature was raised to 130-150 °C and refluxed for 4-10 h. After the reaction, the system was cooled to room temperature, filtered, washed with water, recrystallized from tetrahydrofuran, and dried in vacuo to obtain intermediate 1.

[0010] S2. Dissolve the intermediate 1 in tetrahydrofuran, add a tetrahydrofuran solution of a carbodiimide condensing agent and a coupling agent in an ice-water bath, and stir for 0.5 to 2 hours; then slowly add a tetrahydrofuran solution containing phenyl diaminophosphorate while stirring continuously, and react under ultrasonic stirring at room temperature for 20 to 24 hours; after the reaction, filter, wash with water, and vacuum dry to obtain the intermediate 2;

[0011] S3. In an anhydrous and oxygen-free environment, add 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, cesium carbonate, palladium acetate, and 1,1'-binaphthyl-2,2'-bisdiphenylphosphine to 1,4-dioxane and stir evenly; raise the temperature of the mixture system to 70-90°C, add intermediate 2, and stir the reaction for 20-24 hours; filter, precipitate the solid with deionized water, and wash the solid with a mixed solution of ethyl acetate and petroleum ether at least twice to obtain a PN-Si type flame retardant.

[0012] The carbodiimide condensation agent is one of 1-ethyl-(3-dimethylaminopropyl (EDC) carbodiimide hydrochloride), diisopropylcarbodiimide (DIC), and N,N-dicyclohexylcarbodiimide (DCC); the coupling agent is one of N-hydroxysuccinimide (NHS) and N-hydroxysulfosuccinimide (Sulfo-NHS); in some embodiments of the specification, the substances used are EDC and NHS, which are used in combination to promote the coupling of carboxyl and amine groups and reduce the generation of by-products.

[0013] Furthermore, the vacuum drying conditions in S1 to S3 are the same: drying at a temperature of 100 to 120° C. for 6 to 8 hours.

[0014] Furthermore, the molar ratio of DOPO to 4-bromocinnamic acid in S1 is (1.1-1.3):1.

[0015] Furthermore, the molar ratio of the intermediate 1 to phenyl diaminophosphoester in S2 is (2.2-2.5):1; a slight excess of the intermediate 1 can ensure the coupling effect of the carboxyl group and the amine group.

[0016] Furthermore, the molar ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to intermediate 2 in S3 is (1.1-2.0):1.

[0017] Furthermore, the average molecular weight of the NP-Si type flame retardant is 3000 to 30000 Da.

[0018] Another aspect of the present invention provides a method for preparing a washable flame-retardant cotton fabric, which is characterized by comprising the following steps:

[0019] (1) Pretreatment of the cotton fabric surface: rinsing the cotton fabric in a sodium hydroxide solution to activate the cotton fabric surface; then repeatedly washing with deionized water until the washing solution is nearly neutral, and drying for later use;

[0020] (2) Preparation of flame retardant finishing liquid: Weigh the synthesized PN-Si type flame retardant and dissolve it in 75% to 95% by volume of ethanol solution to obtain a flame retardant finishing liquid with a mass concentration of 20% to 40%;

[0021] (3) The flame retardant finishing liquid obtained in (2) is used to flame retardantly finish cotton fabric by the process of padding, baking and drying to obtain washable flame retardant cotton fabric.

[0022] Furthermore, the concentration of the sodium hydroxide solution in step (1) is 1.0-2.5 mol / L, and the rinsing time is 12-18 h; the padding parameters in step (3) are: two dips and two pads, the padding pressure is 0.1-0.4 Pa, and the liquid rate is 90%-120%; the baking temperature is 140-170° C., the baking time is 2-5 min; and the drying temperature is 90-100° C.

[0023] Beneficial effects of the present invention:

[0024] The present invention chemically bonds different flame retardant groups to the same molecule to form a NP-Si type flame retardant containing multi-group flame retardant molecules, which gives it excellent thermal stability, self-charring ability and flame retardant efficiency. On the one hand, the interaction between different flame retardant groups produces a more efficient group synergistic flame retardant mechanism; on the other hand, through chemical bonding, phosphaphenanthrene, amine, and siloxane groups form an aggregated structure on the molecular scale, which is conducive to obtaining a more efficient group aggregation flame retardant effect.

[0025] The present invention finishes the synthesized NP-Si type flame retardant onto cotton textiles, and can obtain cotton fabrics with water-resistant and flame-retardant effects. The results show that when the cotton fiber is loaded with flame retardants of three elements of Si-PN, its flame retardant effect and thermal stability are greatly improved. Cotton fabric fibers finished with 20g / L flame retardant can pass the UL94 vertical combustion test, and the after-flaming time and smoldering time are both 0. The finished cotton fibers maintain the whiteness and mechanical properties of the cotton fabric; at the same time, hydrogen bonds can occur between the amine groups in the flame retardant system and the cotton fiber molecules, and the flame retardant properties and water washing resistance of the cotton fabric are simultaneously achieved: the cotton fabric still has good flame retardant properties after 50 washes. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0027] Figure 1 The thermal weight loss curves of three NP-Si flame retardants;

[0028] Figure 2 It is the infrared absorption spectrum of NP-Si type flame retardant 3;

[0029] Figure 3 Schematic diagram of the synthesis route of NP-Si type flame retardant. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] Cotton fabric: warp and weft yarn densities are 330 yarns / 10cm and 315 yarns / 10cm respectively, limiting oxygen index is 18.2%, Shanghai Lingda Textile Co., Ltd.;

[0034] DOPO (97% AR), EDC (C 8 H18 N 3 Cl, 98%), N-hydroxysuccinimide NHS (C 4 H 5 NO 3 , 98% AR) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0035] 4-Bromocinnamic acid (C 9 H 7 O 2 Br, 99% AR), Shanghai Huayuan Century Trading Co., Ltd.;

[0036] Phenyl diaminophosphoryl ester (C 6 H 9 N 2 O 2 P, 98% AR), tetrahydrofuran (THF), ethyl acetate and dimethylformamide (DMF), cesium carbonate, palladium acetate, 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, and 1,4-dioxane were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0037] 1,3-Bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane(C 10 H 28 N 2 OSi 2 , BTMDS), AR, Beijing Myrida Technology Co., Ltd.

[0038] Tetrahydrofuran and DMF were dehydrated before the experiment, and the other reagents were used without further purification.

[0039] Preparation Example 1

[0040] A NP-Si type flame retardant is synthesized by the following steps:

[0041] S1: A four-necked round-bottom flask with a strong stirrer, a condenser and a thermometer was filled with nitrogen, and then 0.55 mol of DOPO was added to tetrahydrofuran under a nitrogen atmosphere at a concentration of 0.275 mol / L, and the temperature was raised to 90°C after it was completely dissolved; 0.5 mol of 4-bromocinnamic acid was added to the reaction system in multiple portions within 0.5 h, and then the temperature was raised to 140°C for reflux reaction for 8 h; after the reaction was completed, the system was cooled to room temperature and filtered; recrystallized from tetrahydrofuran and vacuum dried at 100°C for 8 h to obtain intermediate 1. The yield of 1 was 95.8%.

[0042] S2: 0.3 mol of intermediate 1 was dissolved in tetrahydrofuran to prepare a 2 mol / L solution, and 0.05 mol of EDC condensing agent in tetrahydrofuran solution (concentration of 0.05 mol / L) and 0.01 mol of NHS coupling agent in tetrahydrofuran solution (concentration of 0.01 mol / L) were added in an ice-water bath, and activated with stirring for 1 h; then, 0.5 mol of phenyl diaminophosphate in tetrahydrofuran (concentration of 1 mol / L) was slowly added while stirring, and the reaction was carried out under ultrasonic stirring at room temperature for 24 h; after the reaction was completed, the mixture was filtered and washed with water, and then vacuum dried at 100°C for 8 h to obtain intermediate 2; the yield of 2 was 89.5%.

[0043] S3: In an anhydrous and oxygen-free environment, 0.2 mol of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, cesium carbonate, 0.01 mol of palladium acetate, and 0.01 mol of 1,1'-binaphthyl-2,2'-bisdiphenylphosphine are added to 1,4-dioxane and stirred evenly (the concentration of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 2 mol / L); the temperature of the mixture system is raised to 80°C, intermediate 2 is added, and the reaction is stirred for 24 hours; the mixture is filtered, and a solid is precipitated with deionized water. The solid is washed three times with a mixed solution of ethyl acetate and petroleum ether in a volume ratio of 1:1 to obtain a PN-Si flame retardant.

[0044] Preparation Examples 2-3

[0045] PN-Si type flame retardant 2 and PN-Si type flame retardant 3: The preparation method is different from that of PN-Si type flame retardant 1, except that the ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and intermediate 2 is different; the specific ratio is shown in Table 1.

[0046] Furthermore, the yield, molecular weight and thermal weight loss of PN-Si flame retardant were tested.

[0047] Molecular weight: GPC determination, HLC-8420GPC gel permeation chromatography, TSKgel GMHXL (9μm, 7.8mmI.D.×30cm×2); mobile phase: DMF (containing 0.02mol / LLiBr); flow rate: 1.0mL / min; temperature: 35℃; injection volume: 100μL.

[0048] Thermal gravimetric test: PYRIS thermogravimetric analyzer, temperature range from room temperature to 800℃, heating rate of 10℃ / min, gas flow rate of 20mL / min. Take 10mg sample for each test; weighing accuracy ±0.1%; weighing precision ±0.01%; weighing sensitivity <0.1μg. Thermal decomposition curves of different PN-Si flame retardants are shown in Figure 1The corresponding thermal decomposition characteristic parameters are shown in Table 1.

[0049] Table 1 Test results of yield, molecular weight and thermal weight loss of P-N-Si type flame retardant

[0050]

[0051] It can be seen from the molecular weight test results in Table 1 that the higher the concentration of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, the faster the rate of the alkylation reaction and the higher the yield, but the degree of polymerization decreases and the molecular weight decreases; when the concentration of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is low, the reaction rate decreases, which can promote the extension of the polymer chain and increase the molecular weight.

[0052] from Figure 1 It can be seen that the three PN-Si flame retardants begin to thermally decompose at 300℃~400℃, and the initial decomposition temperatures of NP-Si flame retardants 1, 2, and 3 are 336℃, 353℃, and 382℃, respectively. This stage is because the CP bond (305kJ / mol), CN bond (305kJ / mol) with lower bond energy in the flame retardant and the long fatty chain (CC bond energy 332kJ / mol) are thermally broken; the weight loss after 400℃ mainly comes from the destruction of the contained benzene ring or biphenyl structure and the formation of char residue. The thermal weight loss curves of NP-Si flame retardants 1, 2, and 3 tend to be flat after 530℃, 552℃, and 567℃, respectively, and no longer continue to degrade with the increase of temperature. The residual carbon mass retention rate reaches 30.83%, 33.41%, and 35.83%, respectively. This shows that the introduction of P, N, and Si flame retardant elements and the presence of benzene rings and biphenyl flame retardant functional groups can significantly improve the thermal stability and charring ability of NP-Si type flame retardants.

[0053] Furthermore, NP-Si flame retardant 3 was selected for infrared spectroscopy analysis. The test conditions were: Nicolt Avatar 370 (is10) Fourier transform infrared spectrometer, KBr tablet method for sample preparation, 16 scans, and a resolution of 4 cm -1 , scanning range 400~4000cm -1 . See the infrared spectrum Figure 2 .

[0054] Among them, 3453cm -1 The broad absorption peaks near 3207 cm-1 are due to the N—H stretching vibration of secondary and primary amines. -1 Absorption of NH bond in amide; 2833cm -1 、2916cm -1 The stronger absorption peaks at 2 、-CH3 The characteristic peak of telescopic -1 and 1455cm -1 The peak at 1236cm is the skeleton vibration peak of the benzene ring; -1 、1220cm -1 , P=O, PN bonds appear respectively; 980cm -1 The position is attributed to the stretching vibration of P=O; 1089cm -1 Nearby are the Si-O-Si antisymmetric stretching vibration and PO-Ph absorption vibration peaks, 836 cm -1 The peak of Si-C stretching vibration is 807 cm -1 The peak of Si-O stretching vibration is 755 cm -1 The above infrared absorption spectrum analysis proves the existence of various flame retardant groups in the flame retardant.

[0055] Example 1

[0056] A washable flame-retardant cotton fabric, the preparation steps of which are as follows:

[0057] (1) The cotton fabric was rinsed in a 2 mol / L sodium hydroxide solution for 12 h to activate the surface of the cotton fabric; then it was repeatedly washed with deionized water until the washing solution was nearly neutral, and dried at 90°C for later use; the initial cotton fabric mass m was weighed 1 .

[0058] (2) The PN-Si flame retardant 1 obtained in Preparation Example 1 was dissolved in 75% ethanol solution to obtain a flame retardant finishing liquid with a mass concentration of 20%.

[0059] (3) The flame retardant finishing liquid obtained in (2) is used to flame retardant finish the cotton fabric by the process of dipping, padding, drying and baking: the flame retardant finishing liquid obtained in (2) is used for dipping treatment for 30 minutes; then it is rolled at 0.2Pa with a small rolling mill (two dipping and two rolling), and the liquid carrying rate is 90%; then it is baked at 160°C for 5 minutes; finally, it is washed three times with water to remove the unfixed flame retardant, and the fabric is dried at 90°C. The mass (m 2 ). Cotton fiber weight gain (WPG, %) is calculated according to the following formula:

[0060]

[0061] Example 2-3

[0062] A washable flame-retardant cotton fabric, prepared in the same manner as in Example 1, except that the flame retardants are PN-Si flame retardant 2 and PN-Si flame retardant 3 obtained in Preparation Examples 2 to 3.

[0063] Embodiment 4-7

[0064] A washable flame-retardant cotton fabric, the preparation process of which is compared with that of Example 1, except that the mass concentrations of the flame-retardant finishing liquid are 25%, 30%, 35% and 40% respectively.

[0065] Comparative Example 1

[0066] A cotton fabric omitting the flame retardant finish.

[0067] Comparative Examples 2-3

[0068] A washable flame-retardant cotton fabric, which is different from Example 1 in that the mass concentrations of the flame-retardant finishing liquid used are 5% and 15% respectively.

[0069] Test Case

[0070] The following performance tests were performed on the cotton fabrics of the embodiments and comparative examples. The test results are shown in Table 2.

[0071] 1) Limiting oxygen index (LOI). The limiting oxygen index test was conducted using a JE-5 fully automatic oxygen index tester (Nanjing Jionglei Instrument Equipment Co., Ltd.) in accordance with GB / T 5454-1997 "Textile Combustion Performance Test Oxygen Index Method", with a sample size of 110mm×6mm×2mm; the higher the limiting oxygen index value, the higher the oxygen concentration required for the sample to burn, that is, the more difficult the sample is to burn; when the fabric LOI is ≥26, it is considered a flame-retardant material.

[0072] 2) Vertical combustion performance. The CZF-3 horizontal vertical combustion tester produced by Nanjing Jiangning District Analytical Instrument Factory was used to measure the vertical combustion UL-94 grade of the sample in accordance with the national standard GB / T 8746-2009 "Vertical method for testing combustion performance of textiles"; and the damaged length of cotton fabric was measured in accordance with the standard GB / T5455-2014 "Determination of vertical damage length, smoldering and afterflaming time of textile combustion performance"; the sample size was 130mm×13mm×3.2mm.

[0073] 3) Fabric washability test. The cotton fabric was washed 50 times according to GB / T 17591-1998 "Household washing procedures before fabric burning test", and then taken out and dried, and LOI was tested according to GB / T5454-1997 "Textile burning performance test oxygen index method" to analyze the washability of flame retardant cotton fabric.

[0074] Table 2 Performance test results of embodiments and comparative examples

[0075]

[0076]

[0077] According to Examples 1 to 3 and Comparative Example 1 in Table 2, the LOI value of the cotton fabric without flame retardant finishing is 18.2, which is a very flammable material. The flame retardant finishing liquid configured with the NP-Si type flame retardant provided by the present invention can significantly improve the flame retardant properties of cotton fabrics; and the high molecular weight flame retardant can more efficiently improve the flame retardant properties of cotton fabrics.

[0078] Combined with the test results of cotton fabrics in Example 1, Examples 4 to 7 and Comparative Examples 2 to 3, with the increase of flame retardant finishing agent, the damage length, afterflame time and smoldering time are continuously shortened, and the vertical burning effect of cotton fabric is continuously improved; and when the concentration reaches 25% and above, cotton fabric has excellent flame retardant effect: cotton fabric is rapidly carbonized when burning vertically, afterflame and smoldering time are both 0, the damage length is <80mm, and the minimum can be reduced to 55mm. After washing 50 times, the damage length of cotton fabric increases slightly; the fabric still extinguishes itself and has certain flame retardant properties; even the washable flame retardant cotton fabric with the minimum LOI value, after washing, the LOI drops to 26.2, which is still a flame retardant material, indicating that the thermal stability and durability of the coated cotton fabric are very good.

[0079] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A washable flame-retardant cotton fabric, characterized in that: The washable flame-retardant cotton fabric is prepared by treating the cotton fabric with a flame-retardant finishing liquid containing an NP-Si type flame retardant; the molecular structure of the NP-Si type flame retardant is shown in Formula I: Formula Ⅰ.

2. A washable flame-retardant cotton fabric as claimed in claim 1, characterized in that: The NP-Si type flame retardant is synthesized by the following steps: S1. Under nitrogen protection, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was dissolved in tetrahydrofuran, 4-bromocinnamic acid was added to the reaction system within 0.5 h at 80-90 °C, and then the temperature was raised to 130-150 °C and refluxed for 4-10 h. After the reaction, the system was cooled to room temperature, filtered, washed with water, recrystallized from tetrahydrofuran, and dried in vacuo to obtain intermediate 1. S2. Dissolve the intermediate 1 in tetrahydrofuran, add a tetrahydrofuran solution of a carbodiimide condensing agent and a coupling agent in an ice-water bath, and stir for 0.5 to 2 hours; then slowly add a tetrahydrofuran solution containing phenyl diaminophosphorate while stirring continuously, and react under ultrasonic stirring at room temperature for 20 to 24 hours; after the reaction, filter, wash with water, and vacuum dry to obtain the intermediate 2; S3. In an anhydrous and oxygen-free environment, add 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, cesium carbonate, palladium acetate, and 1,1'-binaphthyl-2,2'-bisdiphenylphosphine to 1,4-dioxane and stir evenly; raise the temperature of the mixture system to 70-90°C, add intermediate 2, and stir the reaction for 20-24 hours; filter, precipitate the solid with deionized water, and wash the solid with a mixed solution of ethyl acetate and petroleum ether at least twice to obtain a PN-Si type flame retardant.

3. A washable flame-retardant cotton fabric as claimed in claim 2, characterized in that: The vacuum drying conditions in S1 to S3 are drying at a temperature of 100 to 120° C. for 6 to 8 hours.

4. The washable flame-retardant cotton fabric according to claim 2, characterized in that: The carbodiimide condensation agent in S1 is one of 1-ethyl-(3-dimethylaminopropyl)-carbodiimide hydrochloride, diisopropylcarbodiimide, and N,N-dicyclohexylcarbodiimide; and the coupling agent is one of N-hydroxysuccinimide or N-hydroxysulfosuccinimide.

5. The washable flame-retardant cotton fabric according to claim 2, characterized in that: The molar ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to 4-bromocinnamic acid in S1 is (1.1-1.3):

1.

6. The washable flame-retardant cotton fabric according to claim 2, characterized in that: The molar ratio of the intermediate 1 to phenyl diaminophosphorate in S2 is (2.2-2.5):

1.

7. The washable flame-retardant cotton fabric according to claim 2, characterized in that: The molar ratio of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in S3 to intermediate 2 is (1.1-2.0):

1.

8. The washable flame-retardant cotton fabric according to claim 2, characterized in that: The average molecular weight of the NP-Si type flame retardant is 3000 to 30000 Da.

9. The method for preparing a washable flame-retardant cotton fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Pretreatment of the cotton fabric surface: rinsing the cotton fabric in a sodium hydroxide solution to activate the cotton fabric surface; then repeatedly washing with deionized water until the washing solution is nearly neutral, and drying for later use; (2) Preparation of flame retardant finishing liquid: Weigh PN-Si type flame retardant and dissolve it in 75% to 95% by volume of ethanol solution to obtain a flame retardant finishing liquid with a mass concentration of 20% to 40%; (3) The flame retardant finishing liquid obtained in (2) is used to flame retardantly finish cotton fabric by the process of padding, baking and drying to obtain washable flame retardant cotton fabric.

10. The method for preparing a washable flame-retardant cotton fabric according to claim 9, characterized in that: The concentration of the sodium hydroxide solution in step (1) is 1.0-2.5 mol / L, and the rinsing time is 12-18 h; the padding parameters in step (3) are: two dips and two pads, the padding pressure is 0.1-0.4 Pa, and the liquid carrying rate is 90%-120%; the baking temperature is 150-170° C., the baking time is 2-5 min; and the drying temperature is 90-100° C.

Citation Information

Patent Citations

  • Flame-retardant finishing method of reactive expansion flame retardants on cotton fabrics

    CN104846639A

  • High-temperature-resistant flame-retardant polyester fiber and preparation process thereof

    CN116770453A

  • Method for preparing flame-retardant cellulosic fibers

    US20210198813A1

  • Compound and wrapping tape consisting of a TPU film

    WO2008151893A1